Kekhasan Pemikiran Misbah Musthofa Dalam Tafsir Al-Iklīl Fī Ma’ānī Al-Tanzīl Dan Contoh Teks Penafsirannya - Anggi Maulana; Mifta Hurrahmi; Alber Oki (ZAD Al-Mufassirin, 2021)
Tafsir Al-Iklil Fī Ma’āni Al-Tanzīl is the work of Misbah Musthofa (1916-1994 ). Written using pegon script with the aim of writing to carry out Islamic law as much as possible and its contents ,the understand the quran and its contents. This interpretation is used as a medium for preaching. Misbah Mustafa wrote Tafsir Al-Iklil Fī Ma’āni Al-Tanzīl  for 8 years starting from 1977 to 1985 AD. In his book of commentaries, Misbah Mustafa studies a lot about the phenomena of problems that arise in society. This book consists of 30 volumes, each volume contains 1 juz of Quran. The method used by Misbah Mustafa in writing his tafsir is the tahlili method. The author uses the library method in finding data related to this paper.